Genome-wide analysis and expression of the aquaporin gene family in Avena sativa L. - Zhou, Xinyue; Yi, Dengxia; Ma, Lin; Wang, Xuemin (Frontiers in Plant Science, 2024)
Background Oat (Avena sativa L.) belongs to the early maturity grass subfamily of the Gramineae subfamily oats (Avena) and has excellent characteristics, such as tolerance to barrenness, salt, cold, and drought. Aquaporin (AQP) proteins belong to the major intrinsic protein (MIP) superfamily, are widely involved in plant growth and development, and play an important role in abiotic stress responses. To date, previous studies have not identified or analyzed the AsAQP gene family system, and functional studies of oat AQP genes in response to drought, cold, and salt stress have not been performed. Methods In this study, AQP genes (AsAQP) were identified from the oat genome, and various bioinformatics data on the AQP gene family, gene structure, gene replication, promoters and regulatory networks were analyzed. Quantitative real-time PCR technology was used to verify the expression patterns of the AQP gene family in different oat tissues under different abiotic stresses. Results In this study, a total of 45 AQP genes (AsAQP) were identified from the oat reference genome. According to a phylogenetic analysis, 45 AsAQP were divided into 4 subfamilies (PIP, SIP, NIP, and TIP). Among the 45 AsAQP, 23 proteins had interactions, and among these, 5AG0000633.1 had the largest number of interacting proteins. The 20 AsAQP genes were expressed in all tissues, and their expression varied greatly among different tissues and organs. All 20 AsAQP genes responded to salt, drought and cold stress. The NIP subfamily 6Ag0000836.1 gene was significantly upregulated under different abiotic stresses and could be further verified as a key candidate gene. Conclusion The findings of this study provide a comprehensive list of members and their sequence characteristics of the AsAQP protein family, laying a solid theoretical foundation for further functional analysis of AsAQP in oats. This research also offers valuable reference for the creation of stress-tolerant oat varieties through genetic engineering techniques.